CRISPR/Cas9 System-Mediated Gene Editing in the Fujian Oysters (Crassostrea angulate) by Electroporation - Jin, Kaidi; Zhang, Baolu; Jin, Qianqian; Cai, Zhongqiang; Wei, Lei; Wang, Xiaomei; Zheng, Yanxin; Huang, Baoyu; Zhang, Meiwei; Qi, Yitao; Liu, Yaqiong; Wang, Xiaotong (Frontiers in Marine Science, 2021)
The Fujian oyster (Crassostrea angulate) is an important marine bivalve mollusk with high economic value. Gene function research and gene editing techniques have broad application prospects in oyster. The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system has been widely used for genome engineering in many species. CRISPR-mediated gene editing has also been used successfully in the Pacific oyster through direct delivery of the CRISPR/Cas9 components into oyster embryos by microinjection. However, the low throughput and operational difficulties associated with microinjection is one of the factors limiting the widespread application of CRISPR/Cas9 in oysters. In this study, we attempted to deliver the CRISPR/Cas9-system into the embryos of C. angulate by electroporation. An all-in-one CRISPR/Cas9 vector plasmid was used as CRISPR/Cas9 system in this study. Electroporation was carried out using both eggs and blastula larvae. A large number of larvae became malformed or die after electroporation. A single base substitution mutation was detected in the D-larvae developed from electroporated eggs. Our results demonstrate that the CRISPR/Cas9 system can be delivered into embryos of C. angulate for gene editing by electroporation, which provides a reference and will further contribute to the future application of electroporation in mollusks.